2020
DOI: 10.1007/s00264-020-04635-5
|View full text |Cite
|
Sign up to set email alerts
|

Operational strategies of a trauma hub in early coronavirus disease 2019 pandemic

Abstract: Purpose The "Spedali Civili", one of the largest hospitals in the Italian region most affected by SARS-CoV-2 infection, is managing a large number of traumatic injuries. The objective of this article is to share our operational protocols to deliver an appropriate hospital trauma care in the context of the COVID-19 pandemic. Methods We changed our work shifts, in consideration of the high number of patients; colleagues from smaller hospitals in the area joined us to increase the number of surgeons available. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 18 publications
0
33
0
2
Order By: Relevance
“…4 Preliminary reports on trauma center admissions have been mixed, with one study in New Zealand showing a 43% reduction 5 at their level I trauma center, while studies in the UK and Singapore reported no meaningful change in volume. 4 6 There is an abundance of medical literature describing the effects of the pandemic on hospital planning and injury patterns, particularly in international settings that were affected early in the pandemic, including China [7][8][9] and elsewhere in Asia, 4 10 11 the UK 6 12-16 and elsewhere in Europe, [17][18][19][20][21][22][23] as well as Australia and New Zealand. 5 24 There have also been numerous studies determining the effects of the pandemic on specific types of injuries, including burns, 25 head injuries, 19 26 facial injuries, 12 14 domestic violence 27 and especially orthopedic injuries, 8 13 15 16 23 28 29 as they typically represent the most common injuries due to trauma.…”
Section: Introductionmentioning
confidence: 99%
“…4 Preliminary reports on trauma center admissions have been mixed, with one study in New Zealand showing a 43% reduction 5 at their level I trauma center, while studies in the UK and Singapore reported no meaningful change in volume. 4 6 There is an abundance of medical literature describing the effects of the pandemic on hospital planning and injury patterns, particularly in international settings that were affected early in the pandemic, including China [7][8][9] and elsewhere in Asia, 4 10 11 the UK 6 12-16 and elsewhere in Europe, [17][18][19][20][21][22][23] as well as Australia and New Zealand. 5 24 There have also been numerous studies determining the effects of the pandemic on specific types of injuries, including burns, 25 head injuries, 19 26 facial injuries, 12 14 domestic violence 27 and especially orthopedic injuries, 8 13 15 16 23 28 29 as they typically represent the most common injuries due to trauma.…”
Section: Introductionmentioning
confidence: 99%
“…Seven articles 5 , 6 , 7 , 8 , 13 , 19 , 20 mention and recommend about having separate designated OR for COVID positive or suspected patients. Hospitals should also designate separate specific corridors/ walkways for transfer of COVID positive or suspected patients to OR 10 .…”
Section: Discussionmentioning
confidence: 99%
“…Full face shield is preferred to protective eye goggles. Multiple surgical masks should also not be u as alternative to N95/FFP2 as it also fails to filter virus loaded particles 8 . In addition to the type of masks used, the fitting and sizing of the mask is of utmost importance.…”
Section: Discussionmentioning
confidence: 99%
“…Some of the papers included have looked at problems particular to the orthopaedic specialist and department during the health crisis; Casiraghi et al from Italy report on 'Operational Strategies of a Trauma Hub in Early COVID-19 Pandemic', invaluable experience from one of the first European countries to see a peak in cases on how to keep a trauma centre running effectively [2]. This perspective is supplemented by other Italian contributions from Grassi et al, detailing 'The Covid-19 outbreak' [3] as well as 'The chronic of a silent war' by Benazzo and coll [4].…”
Section: Vikas Khanduja Marius M Scarlatmentioning
confidence: 99%
“…Despite the cost, however, out of this pandemic we have seen the emergence of a real spirit of hope, collaboration and generosity [1][2][3][4]. Makeshift hospitals being made in record time to cope with the increasing demand in beds, community support and volunteering pouring out for the elderly and the infirm, international collaborative research in search of a vaccine and many more heart-warming stories celebrating the human spirit.…”
mentioning
confidence: 99%